Assessing Compatibility of Growth Indices of Exclusive Breast-feeding Infants to World Health Organization Growth Standards: A Regional Study in Urban Centers of Iran - Saeedeh TARVIJESLAMI; Maryam ESLAMI; Mahdieh VAHEDI; Seyedehsara BAYESH; Hosain NASIRIAN (Tehran University of Medical Sciences, 2020)
Background: Breastfeeding as a normal way provides all the nutrients for infant's growth and development. World health organization (WHO) growth standards are definitely recommended for breastfed infants monitoring. We attempted to compare the growth of males and females exclusively breastfed infants founded on WHO standards and to assess whether the infant growth is consistent with the growth standard of WHO. Methods: Data was roundup from two surveys, a clinic owned by a physician and four public health organization instructed from 2011-2016 containing 500 healthy infants exclusively breastfed, aged birth up to 6 months, in northeastern Iran, Mashhad. Results: Growth criteria for male infants were significantly higher than females P<0001. Founded on WHO standards, the growth was different between female and male infant's weight at 1-2 months P=0.034. Moreover, height at birth and 5-6 months of age P=0.003 and <0.001. Furthermore, newborns' head circumference P=0.003, and 4-5 months of age, P=0.019. There were no significant differences at the other months of age between growth indexes of males and females. Growth indexes in 70% of infants in these months of age were observed within normal range and similar to WHO standards, especially in male infants. Conclusion: Growth indexes were similar to WHO standards. However, in Iran, these breastfed growth standards are not respected. Implementing WHO standards may have important implications for child health programs, which leads to monitoring of correct growth of breastfed infants and preserving exclusive breastfeeding with developing nutritional intervention program.